Pelatihan Pengemasan Gula Jawa Di Desa Slumbung Kecamatan Ngadiluwih - Rochana, Siti; Dusea Widya Dara, Made Ayu; Wulanningrum, Resty; Swanjaya, Daniel; Irawan, Rony Heri; Iqbal Jauhari, Nur Mohamad Iqbal Jauhari (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Javanese sugar at this time is also the sugar that is needed by society apart from granulated sugar, many benefits can be obtained from brown sugar besides granulated sugar as an alternative to sweeteners in various processed dishes. In Slumbung Village, many farmers plant sugarcane on their land, with so much sugarcane in Slumbung Village, therefore many people use the sugar cane to be processed into Javanese sugar. After conducting a survey on the average packaging of Javanese Sugar products, they were still not packaged properly so that Java Sugar could not last long. There is also no packaging design and it seems less attractive. It is hoped that if the packaging and product packaging design are more attractive it will help increase sales of community products in Slumbung Village, so that they can be marketed in the modern market. The objectives of this PKM activity are: 1) to provide training on how to pack good products and make Javanese sugar products last a long time; 2) provide training on how existing designs will be used for product packaging; 3) accompany partners until they can actually implement the training they have received. This PKM activity is carried out for 6 months until the partners can actually implement the training that has been obtained.